Civil Engineering Handbook - Church Urquhart Leonard (Mcgraw Hill Book Company, 1959)
Contributors, Preface, Surveying, Railway and Highway and Airport Engineering, Mechanics of Materials, Hydraulics, Stresses in Framed Structures, Steel Design, Cement and Concrete, Reinforced Concrete, Soil Mechanics and Foundations, Sewerage and Sewage Disposal, Water Supply and Treatment, Index.